Active Fold‐Thrust Belt to Foreland Transition in Northern Adria, Italy, Tracked by Seismic Reflection Profiles and GPS Offshore Data. Issue 11 (14th November 2020) - Pezzo, G.; Petracchini, L.; Devoti, R.; Maffucci, R.; Anderlini, L.; Antoncecchi, I.; Billi, A.; Carminati, E.; Ciccone, F.; Cuffaro, M.; Livani, M.; Palano, M.; et al.
Abstract: The Adria microplate is the foreland of the oppositely verging Apennines and Alps or Dinarides fold‐thrust belts associated to the related subduction zones. Along its western margin, the Adria plate hosts the active Northern Apennines accretionary prism, which is buried under the Adriatic Sea and the Po Plain. The interpretation of seismic reflection profiles and borehole data allowed us to define the geometry of the transition from the Apennines fold‐thrust belt to its undeformed foreland. Moreover, continuous GPS (CGPS) data from offshore hydrocarbon platforms anchored to the seabed of the northern Adriatic plate allow to measure present‐day kinematics. Although the CGPS signals are affected by non‐tectonic components associated with hydrocarbon extraction, the integration of geodetic analysis, subsurface geological reconstructions, and analytical modeling allowed us to constrain the ongoing tectonic activity. Shortening is currently accommodated by aseismic slip along the basal detachment, likely accumulating elastic energy along the frontal ramp that may eventually seismically slip. Our multidisciplinary study suggests that the study area may not be sheltered from relevant seismic sequences similar to the Mw 6 Emilia 2012 events and that the occurrence of potential seismogenic sources in the area should be carefully evaluated. Similar studies may be useful to constrain the present‐day activity in other marine areas and to identify potential and hitherto unrecognized seismogenic sources along the entire Apennines belt and other accretionary prisms worldwide. Key Points: Seismic reflection profiles in the northern Adriatic Sea allow to reconstruct the Apennines fold‐thrust belt geometry and its foreland Offshore CGPS data allow computation of the active shortening in the accretionary prism Analytical modeling provides a first‐order estimation of the current slip rate of the unlocked and locked surfaces of the basal decollement